Improving Teacher Professional Competence Through Clinical Supervision - Mastuti, Sri; Enriquez, Alexis Arizabal; Gunarhadi, Gunarhadi (PPSDP International Journal of Education, 2022)
The purpose of this study is to identify and describe the use of clinical supervision in developing teacher’s competency at SMA Tri Dharma Palembang. This is accomplished through the use of a qualitative technique with a case study design. Data collection methods include observation, interviews, and documentation, with a single data analysis. The results revealed that the application of clinical supervision at Tri Dharma High School Palembang went smoothly through three stages, namely pre conference, observation, and post conference, and boosted teacher competency in controlling the learning process. This study is new because it attempts to investigate the growth of teacher’s professional competence connected with the adoption of clinical supervision in senior high schools. This study is likely to help school principals who seek to increase teacher professionalism by using clinical supervision appropriately.